KONSEKUENSI SOSIAL MEDIA TEKNOLOGI KOMUNIKASI BAGI MASYARAKAT - Zulkarnaen Nasution (Universitas Tribhuwana Tunggadewi, 2011)
Usage of technological communications media in life of society person this time, can be seen to the number of used by personal computer ( notebook) in everyday life. Besides easily can be seen by society, specially at urban society using telephone of seluler (hand phone). These days usage of communications media have represented requirement of fundamental to individual, group, and also organization. Positive impact which felt by the following society : ( a) Can create experience learn having a meaning, ( b) Facility interaction of intra personal, ( c) Enrich experience learn social values of culture, ( d) Can alter atmosphere learn social values of culture become actively, ( e) Improve efficiency and productivity, and ( f) Watering down sending and acceptance of information. This article conclude that social Consequence of technological communications media impact can be damage or constructive, negative or positive either through physical nor thingsly having the character of nonphysical. Often we see this time exactly human being of controlled by communications technology, its meaning she or he not yet understood is correct of benefit will from communications technology, up at which that information technology expand, to what end in fact information technology. Though if, understanding of information century will this time possible we can control information technology for the progress of x'self even one who is in around society, or even he/she will create new matter of growth of communications technology and information.